A Facility-Based Study of Severity of Pain Among Patients with Temporomandibular Myofascial Pain Syndrome - Okoh M; Onyia N; Azeez O; Okoh DS (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Myofascial pain syndrome is the most common temporomandibular joint (TMJ) disorder. Objective: To measure pain severity among patients with temporomandibular myofascial pain syndrome using the Visual Analogue Scale (VAS), and to relate pain severity to age and gender. Methods: A cross-sectional study of patients who presented with TMJ pain and were diagnosed with TMJ myofascial pain syndrome was conducted. Data were collected using a structured questionnaire and were statistically analysed. Results: Out of a total of 603 patients, 18 (3.0%) had temporomandibular myofascial pain syndrome. They were aged 22-78 years with female preponderance (11; 61.1%) and a female-to-male ratio of 1.6:1. The majority of the patients had mild pain (7/18; 38.9%). The mean VAS score for the patients in this study was 5.8+2.6. The female patients experienced more severe pain (5/11; 45.4%), compared to males. Conclusion: There was a female preponderance in TMJ myofascial pain syndrome, with a mean VAS pain score of 5.8+2.6. Severe pain was mostly reported by female patients while the male patients often present with mild pain.